The impact of Popular Health Insurance "Seguro Popular"on diabetes mortality in Mexico, 1999-2014 - Eduardo Hernández-Garduño; Abigaíl Yasmín Jiménez-Cortez (Instituto Nacional de Salud Pública, 2017)
Dear editor: Diabetes mellitus (DM)has been the first cause of death in females  and the second  cause in males since 2003 in Mexicans aged 20 to 79.1 A study from 1980 to 1999 showed that the age-standardized mortality rate of DM (ASMR) in Mexico increased dramatically parallel to ratesof obesity.2 In 2004, half of Mexicans had no health insurance and the Popular Health Insurance or "Seguro Popular" (SP) was introduced3 extending health insurance nationwide mainly for the poor. Among other diseases, SP covers free diagnostics, hospitalization and medical treatmentfor DM. By 2015, 57.1 million people in the country were enrolled in SP.4 In this letter we report the annual percent change (APC) of DM's ASMR from 1999 to 2014 in Mexicans aged 20 to 79 to determine whether the introduction of SP in 2004 has impacted DM mortality.